Kron 3: a fourth intermediate age cluster in the SMC with evidence of multiple populations - Hollyhead, Katie; Lardo, C.; Kacharov, Nikolay; Bastian, Nate; Hilker, Michael; Rejkuba, Marina; Koch-Hansen, Andreas; Grebel, Eva K.; Georgiev, Iskren Y. (Arxiv, 2018)
We present the results of a spectroscopic study of the intermediate age (approximately 6.5 Gyr) massive cluster Kron 3 in the Small Magellanic Cloud. We measure CN and CH band strengths (at 3839 and 4300 Angstroms respectively) using VLT FORS2 spectra of 16 cluster members and find a sub-population of 5 stars enriched in nitrogen. We conclude that this is evidence for multiple populations in Kron 3, the fourth intermediate age cluster, after Lindsay 1, NGC 416 and NGC 339 (ages 6-8 Gyr), to display this phenomenon originally thought to be a unique characteristic of old globular clusters. At 6.5 Gyr this is one of the youngest clusters with multiple populations, indicating that the mechanism responsible for their onset must operate until a redshift of at least 0.75, much later than the peak of globular cluster formation at redshift ~3.